Data Saves the Whales!. Issue 2 (18th September 2020) - Koval, Jayma; Rosen, Jeff; Alemdar, Meltem; Usselman, Marion
Data Saves the Whales! was developed as part of the Advanced Manufacturing and Prototyping Integrated to Unlock Potential (AMP-IT-UP) project, funded by the National Science Foundation through its Math and Science Partnership program. A central outcome of the AMP-IT-UP project was the development of 1-week modules for core middle school math and science courses that were aligned with best practices as put forth in the Next Generation Science Standards and Standards of Mathematical Practice. Data Saves the Whales! is a middle school mathematics module that is set within a marine ecosystem. It focuses on independent and dependent variables and Cartesian coordinate graphing, and on math practices related to data representation—i.e. how data can be represented in different ways to communicate various messages to an audience. Students engage in a simulated investigation to collect oceanographic data, meant to mimic the experimental procedures used by marine scientists when collecting samples, and learn different methods of graphing the data to effectively communicate their findings. This module features work conducted by the research team of Dr. Ellery Ingall, Professor of Earth and Atmospheric Science at Georgia Tech, and integrates math skills with marine science and the concepts of food webs and the interdependence of organisms.